MTHFR C677T and TS 5’-UTR 3R/3R Gene Polymorphism in Methotrexate-Resistant Childhood Acute Lymphoblastic Leukemia - I Dewa Gede Ugrasena; Harianto Notopuro; Subijanto Marto Sudarmo; Ketut Sudiana; Djajadiman Gatot; Ponpon Idjradinata (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Childhood acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy in Indonesia and often treated by methotrexate (MTX). Though it can be cured in 30-60% of patients, MTX resistance remains the major cause of treatment failure in childhood ALL. Previous sudies showed that its anti-leukemic property was moderated by MTX ability to inhibitmethylene tetra hydrofolate reductase (MTHFR) and thymidylate synthase (TS) in folate metabolism. This study investigates the correlation between MTHFR and TS polymorphism and MTX resistance in ALL children.METHODS: A total of 155 subjects obtained from all subjects prior to chemotherapy. DNA from blood samples were extracted and underwent polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) to evaluate MTHFR C677T and TS 5’-UTR 3R/3R polymorphism.RESULTS: There was significant correlation between MTHFR C677T and TS 5’-UTR 3R/3R gene polymorphism with MTX resistance. Subjectswith MTHFR C677T and TS 5’-UTR 3R/3R gene polymorphism were 4 times (p=0.007) and 6.4 times (p=0.001) more likely to be MTX resistant than those without gene polymorphisms, respectively.CONCLUSION: MTHFR C677T andTS 5’-UTR 3R/3R represent dominant gene polymorphism related to MTX resistance in childhood ALL.KEYWORDS: gene polymorphism, folate metabolism, acute lymphoblastic leukemia